The interdependence of professional and physical readiness for future officers of the Air Force - V.M. Krasota; O.M. Olkhovy (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Purpose. Determination of interdependence of the initial level of formation and development of general and applied physical cadets' qualities with the level of their preparedness for the performance of official functions and typical tasks of professional activity. Material, methods. 173 graduate cadets and 58 experts took part in the research. We used the following methods: theoretical analysis, generalization of scientific sources, ascertaining experiment, mathematical statistic. Results. Conducting of the ascertaining experiment allowed us to identify: the level of applied physical cadets' qualities formation is significantly lower than evaluative level of their general physical qualities: power by 0,27 points, speed by 0,44 points and aerobic endurance by 0,19 points; the strong straight correlation dependence (r=0,327) of the initial level of development of applied physical qualities of future officers of the Air Force with the level of their readiness to perform official functions and typical tasks of professional activity. Conclusions. The presence of significantly better formed applied physical characteristics of young officers with a high professional readiness level confirms the expediency to continue research in the chosen direction.